?SEEDLING VIGOR AND GENETIC VARIABILITY FOR RICE SEED, SEEDLING EMERGENCE AND SEEDLING TRAITS - ALI, SVED SULTAN; JAFRI, S J H; JAMIL, M.; IJAZ, M. (Biological Sciences - PJSIR, 1994)
Eleven local rice cultivars including Basmati 370 were evaluated for seedling vigor. Three groups of traits were evaluated viz; seed traits (seed density. seed volume. see weight. paddy length and grain length). seed emergence traits (emergence %. emergence index and emergence rate index). and seedling traits (fresh root length, dry root weight, root to shoot ratio and relative root weight). Genetic variabil ity and heri tabili ty estimates for seed weight, emergence percent- age, root length, dry root weight, seed weight and relative root weight were observed significant, respectively. Seed density, relative root weight, emergence rate index and root to shoot ratio were relatively more amenable to improvement. Relative expected genetic advance was the function of heritability and coefficient of phenotypic variability, latter being more important.